Structuring the Inside of a New-born Business – Case of a Consulting Service Company - Rastrollo-Horrillo, María Ángeles; Savall, Amandine (My University, 2016)
When starting a new business, most entrepreneurs usually focus on the external aspects in order to make their new business successful. Consequently, most research in entrepreneurship has been focused on the external factors to explain the high rate of entrepreneurial failures. But there is also a lack of consideration of the internal aspects by the new entrepreneurs. This paper focuses on these internal aspects and how to help a new business implementing an internal strategy.
Keywords: Éxito en los negocios; Internal strategy; entrepreneurship; SEAM; Management Consulting; Socio-Economic